The relationships between lens diameter and ocular biometric parameters: an ultrasound biomicroscopy-based study - Huang, Zhiqian; Qi, Jiao; Cheng, Kaiwen; Liu, Shuyu; Zhang, Keke; Du, Yu; Lu, Yi; Zhu, Xiangjia (Frontiers in Medicine, 2024)
Purpose: This study aims to explore the relationships between lens diameter (LD) measured with ultrasound biomicroscopy (UBM) and ocular biometric parameters. Methods: Ocular biometric parameters including axial length (AL), white-to-white distance (WTW), anterior chamber depth (ACD), lens thickness (LT) and anterior segment length (ASL) were measured with IOL-Master 700, and the direct measurement of LD was conducted through UBM (ArcScan Insight 100). Relationships between LD and ocular biometric parameters were then investigated. Eyes with AL ≥ 28 mm were defined as eyes with extreme myopia, and eyes with AL < 28 mm were defined as eyes without extreme myopia. Results: A total of 194 eyes from 194 subjects were included. The mean LD was 9.58 ± 0.49 mm, ranging from 8.60 to 10.96 mm. According to univariate analysis, larger LD was associated with elder age, male gender, larger WTW, ACD and ASL (all P<0.05). Meanwhile, the LD was positively correlated with AL in eyes without extreme myopia (P<0.05), but not in eyes with extreme myopia (P>0.05). Backward stepwise regressions revealed that a larger LD was associated with larger WTW, ASL and AL in eyes without extreme myopia (all P<0.05), while ASL was the only significant variable in eyes with extreme myopia (P<0.05). Conclusion: Larger WTW, ASL and AL in eyes without extreme myopia, as well as longer ASL in eyes with extreme myopia indicated a larger LD, which provides guidance in personalized surgical choice and promises ideal visual outcomes.